Catalytic gasification of dewatered sewage sludge in supercritical water: Influences of formic acid on hydrogen production. (23rd February 2016) - Fan, Y.J.; Zhu, W.; Gong, M.; Su, Y.; Zhang, H.W.; Zeng, J.N.
Abstract: Promoting hydrogen production from supercritical water gasification of dewatered sewage sludge at low temperatures has become the essential to realization of technology resource utilization. Here we report supercritical water gasification of dewatered sewage sludge in a batch reactor. Total gas yield increased as the amount of formic acid increased, with hydrogen yield increasing significantly from 0.16 to 10.07 mol/(kg organic matter) as the formic acid increased from 0 to 6 wt%. The amount of undesired phenols in the liquid products was reduced and char in solid residue was also suppressed. An intermediate reaction was also conducted to investigate to the mechanism by which formic acid promoted hydrogen production. Results indicated that formic acid acted as an acid hydrolysis agent and an effective hydrogenating agent that facilitated rapid hydrolysis of carbohydrates to produce small molecules and effectively suppressed polymerization. Overall, the method developed herein has the potential to promote hydrogen production by radical reaction. Graphical abstract: Highlights: Sewage sludge with or without formic acid were gasified in supercritical water. H2 yield reached up to 10.07 mol/kg organic matter with 6 wt% formic acid. Formic acid effectively suppressed the formation of phenols and char. Formic acid acted as both acid hydrolysis agent and effective hydrogenating agent.